Two Potential Syphilis Vaccine Candidates Inhibit Dissemination of Treponema pallidum - Xu, Man; Xie, Yafeng; Zheng, Kang; Luo, Haodang; Tan, Manyi; Zhao, Feijun; Zeng, Tiebing; Wu, Yimou (Frontiers in Immunology, 2021)
Syphilis, caused by the spirochete Treponema pallidum subspecies pallidum, continues to be a major public health problem worldwide. Recent increases in the number of syphilis cases, in addition to the lack of an efficient vaccine against T. pallidum for humans, highlights an urgent need for the design and development of an efficacious syphilis vaccine. Here, we assess the vaccine potential of the adhesion protein Tp0136 and the outer membrane protein Tp0663. Rabbits were subcutaneously immunized with recombinant proteins Tp0136, Tp0663, or control PBS. Immunization with Tp0136 or Tp0663 generated a strong humoral immune response with high titers of IgG, as assessed by ELISA. Moreover, animals immunized with Tp0136 or Tp0663 exhibited attenuated lesion development, increased cellular infiltration at the lesion sites, and inhibition of treponemal dissemination to distant organs compared to the unimmunized animals. These findings indicate that Tp0136 and Tp0663 are promising syphilis vaccine candidates. Furthermore, these results provide novel and important information for not only understanding the pathogenic mechanisms of spirochetes, but also the development of spirochete-specific subunit vaccines.